Effects of a home-based physical training and activity promotion program in community-dwelling older persons with cognitive impairment after discharge from rehabilitation: a randomized controlled trial - Ullrich, Phoebe; Werner, Christian; Schönstein, Anton; Bongartz, Martin; Eckert, Tobias; Beurskens, Rainer; Abel, Bastian; Bauer, Jürgen M.; Lamb, Sarah E; Hauer, Klaus (The journals of gerontology. Series A, Biological sciences, medical sciences, 2022)
Older people with cognitive impairment (CI) are at high risk for mobility limitations and adverse outcomes after discharge from geriatric rehabilitation settings. The aim was to estimate the effects of a specifically designed home-based physical training and activity promotion program on physical capacity, different aspects of physical activity (PA), and psychosocial status. Patients with mild to moderate CI (Mini-Mental State Examination [MMSE]: 17-26 points) discharged home after rehabilitation were included in this randomized, double-blind, placebo-controlled trial with a 12-week intervention and 12-week follow-up period. The intervention group performed a CI-specific, autonomous, home-based strength, balance, and walking training supported by tailored motivational strategies to foster training adherence and promote PA. The control group participated in an unspecific motor placebo activity. Primary outcomes were physical capacity (Short Physical Performance Battery [SPPB]) and PA (sensor-based activity time).Among 118 randomized participants (82.3 ± 6.0 years) with CI (MMSE: 23.3 ± 2.4) and high levels of multimorbidity, those participants undergoing home-based training demonstrated superior outcomes to the control group in SPPB (mean difference between groups 1.9 points; 95% CI: 1.0-2.8; p < .001), with persistent benefits over the follow-up (1.3 points; 95% CI: 0.4-2.2; p < .001). There were no differences in PA across any time points. Among secondary outcomes, fear of falling and activity avoidance behavior were reduced in the intervention group at all time points, life-space mobility improved short-term.The results demonstrate clinically important benefits of an individually tailored autonomous physical training and activity promotion program on physical capacity and secondary outcomes in different domains in a vulnerable, multimorbid population.ISRCTN82378327
Gesehen am 15.11.2023